A new generalized cascade multilevel converter topology and its improved modulation technique. (28th September 2020) - Shalchi Alishah, Rasoul; Bertilsson, Kent; Hosseini, Seyyed Hossein; Babaei, Ebrahim; Aalami, Mohammadamin; Mohed Ali, Jagabar Sathik; Gharehpetian, Gevork B.
Summary: In this paper, a basic unit for the nine‐level converter is firstly presented. Then, a new developed basic unit topology for the multilevel converter is proposed. This topology comprises several bidirectional and unidirectional switches along with dc voltage sources. In order to increase the number of generated levels, a cascade topology based on the series connection of developed basic units is studied. Due to the extensive nature of the presented cascade multilevel converter, the optimization analysis is presented for generating the maximum number of levels with minimum numbers of IGBTs, drivers, dc voltage sources, and voltage on switches. All required mathematical analysis consisting of switching losses, conduction losses, and voltage on switches is illustrated. In order to indicate the merits of the proposed multilevel converter, comparison results are provided. It is shown that the presented topology uses the least numbers of power electronic components. Also, the voltage on the switches in the presented cascade topology is low. For controlling the switches, a modified triangular carrier signal for dual pulse generation is proposed. The performance of the proposed multilevel converter is proven with experimental results of a typical 25‐level converter. Abstract : This paper introduces a new generalized multilevel converter topology. In order to generating maximum number of levels with minimum components and voltage on switches, optimization results are studied. In order to prove the advantages and disadvantages of proposed converter, comparison analysis is presented. The comparison results prove that the introduced topology requires lower components. For controlling the switches, a modified triangular carrier signal for dual pulse generation is proposed. The performance of proposed multilevel converter is proven with experimental results.